The Influences of Online Brand Communities, Social Media and Member Relationship on Purchase Intention for Luxury Goods: Focus on Taiwan Market - Chen, PAi-Yuan (2011)
In the latest decade, Brand Community has been widely discussed and considered as one of the best ways that the business and customers co-create value to enhance the brand loyalty and purchase intention. In recent years, with the development of Internet, the concept of social media and online brand community is thriving. However, while it is a trend for the business to build an online community through social media, luxury brand companies hesitate to embrace social media and online brand community. Until now, luxury brand companies are increasingly paying more attention to the issues of online brand community and try to deliver brand message through this new marketing tool. Therefore, this research try to provide luxury brand companies an insight of online brand community and have a further exploration on the interaction with the luxury online brand community in Taiwan market.